Uptake of positron emission tomography tracers reflects the tumor immune status in esophageal squamous cell carcinoma. Issue 6 (12th May 2020) - Kuriyama, Kengo; Higuchi, Tamami; Yokobori, Takehiko; Saito, Hideyuki; Yoshida, Tomonori; Hara, Keigo; Suzuki, Shigemasa; Sakai, Makoto; Sohda, Makoto; Higuchi, Tetsuya; Tsushima, Yoshito; Asao, Takayuki; et al.
Abstract: The relationship between the local immune status and cancer metabolism regarding 18 F‐FDG and 18 F‐FAMT uptake in esophageal squamous cell carcinoma (ESCC) remains unknown. The present study examined the correlations between tumor immune status, clinicopathological factors, and positron emission tomography (PET) tracer uptake in ESCC. Forty‐one ESCC patients who underwent 18 F‐FDG PET and 18 F‐FAMT PET before surgery were enrolled in the study. Immunohistochemistry was conducted for programmed death 1 (PD‐1), CD8, Ki‐67, CD34, GLUT1 ( 18 F‐FDG transporter) and LAT1 ( 18 F‐FAMT transporter). ESCC specimens with high tumoral PD‐L1 and high CD8‐positive lymphocytes were considered to have "hot tumor immune status." High PD‐L1 expression (53.7%) was significantly associated with tumor/lymphatic/venous invasion ( P  = 0.028, 0.032 and 0.018), stage ( P  = 0.041), CD8‐positive lymphocytes ( P  < 0.001), GLUT1 ( P  < 0.001), LAT1 expression ( P  = 0.006), Ki‐67 labelling index ( P  = 0.009) and CD34‐positive vessel counts ( P  < 0.001). SUVmax of 18 F‐FDG was significantly higher in high PD‐L1 cases than in low PD‐L1 cases ( P  = 0.009). SUVmax of 18 F‐FAMT was significantly higher in high PD‐L1 ( P  < 0.001), high CD8 ( P  = 0.012) and hot tumor groups ( P  = 0.028) than in other groups. High SUVmax of 18 F‐FAMT (≥4.15) was identified as the only predictor of hot tumor immune status. High PET tracer uptake was significantly associated with cancer aggressiveness and hot tumor immune status in ESCC. PET imaging may be an effective tool to predict tumor immune status in ESCC with respect to immune checkpoint inhibitor sensitivity. Abstract : High positron emission tomography (PET) tracer uptake is significantly correlated with hot tumor immune status (high PD‐L1 expression and infiltrative CD8‐positive T lymphocytes) in ESCC. PET imaging has the potential to select hot ESCC tumors that may benefit from immune checkpoint inhibitors.